The Malvinas/Falklands War of 1982: Lessons for the United States and Latin America - Marcella, Gabriel (1983)
This memorandum explores the lessons of the Malvinas/Falklands war of 1982 for the United States and Latin America. Central to the discussion is an analysis of the motivating factors of the principal actors. The policy implications apply to US military policy, diplomacy, posture toward military governments, arms transfers to Latin America, territorial disputes, and the potential for conflict, and the agenda for inter-American security.